Energetics of nearby stellar bow shocks - Benaglia, Paula (2012)
The latest survey of stellar bow shocks (Peri et al. 2012, A&A, 538, 108) lists 28 candidates detected at IR wavelengths, associated with massive, early-type stars up to 3 kpc, along with the geometrical parameters of the structures found. I present here some considerations on the energetics involved, after the estimation of stellar wind power, infrared flux, stellar bolometric luminosity and radio flux limits for each source. The best candidates for relativistic particle acceleration are highlighted.